Ghost Doctors : Absenteeism in Rural Bangladeshi Health Facilities - Chaudhury, Nazmul (Washington, DC: World Bank, 2014)
Unannounced visits were made to health clinics in Bangladesh to determine what proportion of medical professionals were at their assigned post. Averaged over all job categories and types of facility, the absentee rate was 35 percent. The absentee rate for physicians was 40 percent at the larger clinics and 74 percent at the smaller sub-centers with a single physician. Whether the medical provider lives near the health facility, the opportunity cost of the provider's time, road access, and rural electrification are highly correlated with the rate and pattern of absenteeism.